Nation vs. People: The Axiology of Group Identity - H. T. Sardaryan (Vestnik MGIMO-Universiteta)
The article takes a political philosophical perspective in a conceptual analysis of the nation, focusing on its axiological foundations in the political theories of modernity and postmodernity. It reviews the political philosophy arguments explaining conditions and reasons for individual ethnic groups to become nations. The author emphasizes the role of religion in this process as the main factor in forming national values and identity beyond tribal ties. Despite its importance religion is often dismissed in the research literature on nationalism and nation-building.To stress the importance of collective solidarity for sustaining a national identity, the author juxtaposes the idea of the nation understood as a collective of individuals living in a nationstate united by common values to the idea of the people understood as a collective of individuals living in a nation-state driven solely by their egoistic interests. From this perspective the people render institutions of the national state dysfunctional because of their disrespect for the common values, while the nation strengthens state institutions, making its nationstate resilient to the current global problems.